The Influence of Job Stress and Job Insecurity on Turnover Intention Mediated by Job Satisfaction - Ambar Sasmiaji; Aniek Rumijati; Siti Nurhasanah (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
The study aims to determine the effect of job stress and job insecurity on turnover intention, with job satisfaction as a mediation for PT. Kembang Joyo Sriwijaya employees. This type of research uses quantitative, the population is 112 employees. The sample used is a sample of 88 respondents. The data collection technique is by distributing questionnaires. The data analysis technique is a range of scales and PLS-SEM (Partial Least Square – Structure Equational Model) software. The results obtained show that job stress has a significant effect on turnover intention, job insecurity has a significant effect on turnover intention, work stress has no significant effect on job satisfaction, job insecurity has no significant effect on job satisfaction, job satisfaction has no significant effect on turnover intention, work stress no significant effect on turnover intention with job satisfaction as a mediating variable, job insecurity has no significant effect on turnover intention with job satisfaction as a mediating variable.